Ecological Stoichiometry of the Mountain Cryosphere - Ren, Ze; Martyniuk, Nicolas; Oleksy, Isabella A.; Swain, Anshuman; Hotaling, Scott (Frontiers in Ecology and Evolution, 2019)
Roughly 10% of the Earth’s surface is permanently covered by glaciers and ice sheets and in mountain ecosystems, this proportion of ice cover is often even higher. From an ecological perspective, ice-dominated ecosystems place harsh controls on life including cold temperature, limited nutrient availability, and often prolonged darkness due to snow cover for much of the year. Despite these limitations, glaciers and perennial snowfields still support diverse, primarily microbial communities, though macroinvertebrates and vertebrates are also present. The availability and mass balance of key elements [(carbon (C), nitrogen (N), phosphorous (P)] are known to influence the population dynamics of organisms, and ultimately shape the structure and function of ecosystems worldwide. While considerable attention has been devoted to patterns of existing biodiversity in mountain cryosphere-influenced ecosystems, the ecological stoichiometry of these habitats has been less studied. Understanding this emerging research arena is particularly pressing in light of the rapid recession of glaciers and perennial snowfields worldwide. In this review, we synthesize existing knowledge of ecological stoichiometry, nutrient availability, and food webs in the mountain cryosphere (specifically glaciers and perennial snowfields). We use this synthesis to develop more general understanding of nutrient origins, distributions, and trophic interactions in the mountain cryosphere. We focus our efforts on three major habitats: glacier surfaces (supraglacial), beneath glaciers (subglacial), and adjacent downstream habitats (i.e., glacier-fed streams and lakes). We compare nutrient availability in mountain cryosphere habitats to comparable habitats on continental ice sheets (e.g., Greenland and Antarctica) and show that, in general, nutrient levels are substantially different between the two. Next, we discuss how ongoing climate warming will alter nutrient and trophic dynamics in mountain glacier-influenced ecosystems. We conclude by highlighting the pressing need for future studies to understand spatial and temporal stoichiometric variation in the mountain cryosphere, ideally with direct comparisons to continental ice sheets, before these imperiled habitats vanish completely.